TINJAUAN YURIDIS PEMBENTUKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 2 TAHUN 2022 TENTANG CIPTA KERJA DIKAITKAN DENGAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU/XVIII/2020 - Septiana Ulfah; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In 2020 Indonesia was Constitutional Court Decision Number 91/PUU-XVIII/2020. Inthe decision the Job Creation Law was declared conditionally unconstitutional and gave 2years to complete the revision of the job creation law, but on December 30 2022 theGovernment postponed Government Regulation in Lieu of Law Number 2 of 2022 concerningJob Creation. Since the promulgation of this Perppu, there has been much debate in thecommunity, so there are pros and cons to the enactment of this Perppu. Therefore it isnecessary to know about the process of forming Perppu Number 2 of 2022 concerning JobCreation which is linked to the Constitutional Court Decision Number 91/PUU-XVIII/2020.The purpose of this research was to find out the background for the issuance of Perppu Number2 of 2022 concerning Job Creation by the President, as well as whether the establishment ofPerppu Number 2 of 2022 is in accordance with the Constitutional Court Decision Number91/PUU-XVIII/2020 and to find out how it should be Following up on the Constitutional CourtDecision Number 91/PUU-XVIII/2020 by the President.This research is a normative legal research. Normative legal research that examines andexamines literature or secondary data, by taking quotations from the literature that is relatedto the problem to be studied. As well as a statutory and conceptual approach, in this way thisstudy uses data sources consisting of primary, secondary and tertiary legal materials. Thisstudy also used qualitative data analysis and produced descriptive data.From the results of the discussion and research conducted, several conclusions wereobtained, namely: First, the background to the issuance of Perppu Number 2 of 2022 by thePresident is a matter of urgency that compels and as a continuation in implementing theConstitutional Court Decision 91/PUU-XVIII/2020, Second, the Establishment of PerppuNumber 2 of 2022 is not in accordance with the Constitutional Court Decision Number91/PUU-XVIII-2020. Because the subjectivity of the President which is the main reference forestablishing a Perppu is contained in the Constitutional Court Decision Number 138/PUU-VII/2009. Third, a decision of the constitutional court must be respected but must also beobeyed and maintained in its implementation. The Constitutional Court's Decision RegardingJob Creation as a legal product, the Job Creation Law should have been corrected first.Keywords: Formation of Perppu Number 2 of 2022 concerning Job Creation